The socioeconomic and political determinants of life expectancy in selected countries of the world - Yari, Fatemeh; Agheli, Lotfali; Sadeghi, Hossein; Faraji Dizaji, Sajjad (Social Determinants of Health, 2022)
Background: Longevity as an important measure of health is evaluated based on life expectancy at birth. Since the mid-twentieth century, increasing life expectancy has been considered as an evident indication of demographic change, and most countries have experienced a significant increase in life expectancy. The aim of this study is to identify the economic, social and political determinants of life expectancy and to estimate their related effects. Methods: With the use of panel data obtained from World Bank and GLS approach, we investigate the effects of the factors on life expectancy at birth in selected countries of the world during 2000-2016. Result: The econometric results show that GDP per capita, literacy rate, health expenditure per capita and democracy impact the life expectancy positively. Reversely, GDP per capita squared (in logarithm) influence life expectancy negatively. GDP per capita has the strongest impact on life expectancy. The results indicate at per to 20000 capita income equal US, 1% increase in GDP per capita causes 0.205%, 0.207% and 0.209% increase in life expectancy for total population, males and females, respectively. Conclusion: Positive effect of economic variables of GDP per capita and health expenditure per capita on life expectancy conducts to adopt policies and interventions to improve economic status on a global scale, especially in poor and low income countries. Also, the provision of education opportunities, especially in the low-income countries, and the transition from autocratic political systems to democratic societies may result in longevity and increase the supply of labor in the long-run.